2022
DOI: 10.1155/2022/3955514
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion Detection Using Machine Learning for Risk Mitigation in IoT-Enabled Smart Irrigation in Smart Farming

Abstract: The majority of countries rely largely on agriculture for employment. Irrigation accounts for a sizable amount of water use. Crop irrigation is an important step in crop yield prediction. Field harvesting is very reliant on human supervision and experience. It is critical to safeguard the field’s water supply. The shortage of fresh water is a major challenge for the world, and the situation will deteriorate further in the next years. As a result of the aforementioned challenges, smart irrigation and precision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…e PCA models reached more than 90% of accuracy as a regression coefficient. Here, the dimension reduction technique supports creating a better focus on critical components like choosing the critical aspects, supporting in validating the overall performance and using different aspects to compute the selected attributes [5].…”
Section: Review Of Literaturementioning
confidence: 99%
“…e PCA models reached more than 90% of accuracy as a regression coefficient. Here, the dimension reduction technique supports creating a better focus on critical components like choosing the critical aspects, supporting in validating the overall performance and using different aspects to compute the selected attributes [5].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Image processing refers to the practice of applying various techniques to an image in order to improve it or extract relevant information from it [3,4]. Image processing is a practice that has become more popular in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…According to some researchers, cost-sensitive feedback neural networks were used to classify agricultural products, and the evaluation model was modified based on relevant agricultural product class data [20][21][22][23]. Even though the quality of agricultural products was not taken into account during the application process, the classification effect of this method was insufficient to differentiate them [24]. Other researchers have found that the geometric and morphological characteristics of potatoes can be used to distinguish between distinct quality levels [25].…”
Section: Introductionmentioning
confidence: 99%